Latine Students’ STEM Identity Development: Reflecting on Implicit Biases, Imposter Syndrome, Self-Efficacy, and Support Systems - Alyssa Guadalupe Cavazos; Valerie Leija; Javier Cavazos Vela (Education Sciences, 2025)
This study used an equity ethic framework and a STEM identity model to contextualize and understand Latine students’ perceptions of STEM identity development. The purpose of this study was to investigate how Latine undergraduate students who engaged in STEM coursework perceived their learning experiences and stories of resilience through an equity ethic framework. Data were collected through interviews with 19 Latine college students attending a Hispanic-Serving Institution. Findings revealed the following themes related to Latine students’ STEM identity development and lived experiences in STEM coursework: implicit biases, imposter syndrome, self-efficacy, and support system and resources. Findings highlight the need for institutions of higher education to promote Latine students’ self-efficacy to positively influence STEM identity development while addressing systemic issues, such as implicit biases and imposter syndrome to create safe, growth-enhancing educational climates for students with minoritized identities. We provided implications to cultivate Latine students’ STEM identity development through inclusive teaching and learning practices that foster equitable learning environments as well as institutional resources that support students’ mental health and resilience. Implications of this study can be modeled at HSIs to positively influence STEM identity development and increase Latine students’ persistence in STEM fields.